The introduction of Hydrogen Economy in Cyprus - Panayiotou, Gregoris; Kalogirou, Soteris A. (My University, 2009)
In this paper the introduction of hydrogen to the current energy system of Cyprus is examined. Drivers and barriers towards hydrogen economy are identified and possible solutions are proposed in terms of both policy planning and infrastructure. The introduction of hydrogen to the current energy system of Cyprus will have numerous advantages in all sectors with the main ones being the reduction of the dependency on imported oil, reduction of carbon dioxide emissions, improvement on the local air quality and the environment in general. The only sustainable and renewable path to produce hydrogen in Cyprus is by exploiting the solar potential of the island which is more than enough to cover its energy needs. This can be achieved by either water electrolysis or solar-thermolytic splitting of water.
Keywords: Hydrogen economy; Cyprus; Drivers; Barriers; Sustainable